Wound healing properties of acrostichum aureum and a. speciosum on NIH/3T3 fibroblasts cell line and excisional wound on rabbit - Hendy Putra bin Herman (Kulliyyah of Science, International Islamic University Malaysia, 2014)
Acrostichum aureum or Piai raya has been known for its medicinal value for wound healing treatment among Malays in Malaysia. In this study, the traditional use of this plant together with A. speciosum (Piai lasa) was proven for the first time in vitro and in vivo. Sampling of both plants have been done in Matang mangroves, Taiping, Perak on February 2011. They were dried, ground into fine powder, extracted with water and ethanol to produce extracts and they were fractionated by Vacuum Liquid Chromatography (VLC) to produce fractions. For the first part of study, screening was done on the extracts to identify their phytochemicals content. From the present study, it was reported that both plants have various potential compounds such as tannins, saponins, alkaloids, and flavonoids. Later, antimicrobial study showed that only Staphylococcus aureus was susceptible to the extract treatment and this led to the second part of study which was in vitro wound scratch assay. From MTT assay, the best concentration for the proliferative effect of fibroblasts was 200 µg/mL and hence it was used for the wound scratch assay. There were eights extracts and fractions that showed better mean migration rate but only four were selected to be tested on rabbits. For in vivo study, three groups of four rabbits each were tested using four different extracts with two different concentrations (5 % and 10 %). The excisional wounds were inflicted at the back of the rabbits and treatments were applied once daily until complete healing. Based on wound contraction, epithelization period and histopathological study, it was found that aqueous extract of rhizomes (10 %) and leaves A. aureum (5 %) showed the best wound healing properties with more collagens and fibroblasts proliferation and complete epithelized cells. Therefore, this study has added some novel findings in exploring the use of A. aureum and A. speciosum as wound healing treatement. In conclusion, this study has successfully justified the medicinal use of rhizomes A. aureum in wound healing treatment. In addition to that value, A. speciosum which was not well-studied and other parts of the plant, stems and leaves, also have been reported to possess similar medicinal properties for the first time.